Changes Family Support on Mother's Pregnancy in Preventing Stunting Through Health Education with A Modelling Approach - Irma Muslimin; Rachmawati Rahim (GLOBAL HEALTH SCIENCE GROUP, 2021)
A woman who is pregnant, generally have psychological conditions that will affect their physiological activities. Psychological pressure experienced by pregnant women will cause physical symptoms of fatigue, lethargy, irritability, dizziness, insomnia and laziness. When a pregnant woman is not sensitive to herself and her pregnancy, of course, the role of the family is expected to be able to continue to help the mother in taking care of herself and her pregnancy. This study aims to determine changes in the support of husbands and parents/in-laws of pregnant women in preventing stunting through a modeling approach. The research design used a quasi-experimental design using a non-randomized pre-test post-test with controlled group design. The sample is 50 pregnant women selected by purposive sampling consisting of the treatment group and the control group. Data analysis was carried out by t-test with a significance of 0.05 Data were collected through interviews with respondents using questionnaires after intervention was carried out on respondents The results showed that the husband's support for wife's pregnancy showed an increase in the average value between pre and post-test, namely 19.12 and 22.56 with a p-value of 0.001 (<0.05). Family Support Variables (parents/in-laws, family members) showed an increase in the average value between pre and post-test, namely 10.68 and 12.08 with a p-value of 0.007 (<0.05). There is a significant change in husband and family support for maternal pregnancy through a modeling approach.